A RARE SEEN KIDNEY TUMOR IN CHILDREN: MULTICYSTIC RENAL CELL CARCINOMA: A CASE REPORT - atilgan, dogan (Urology Journal, 2013)
While the incidence of renal cell carcinoma is rising constantly, it remains a relatively uncommon malignancy in the pediatric population. Renal cell carcinomas can present in solid or cystic mass patterns. Multilocular cystic renal cell carcinoma is an uncommon clinical entity in adults and to our knowledge, it has been reported only once in a pediatric patient in the literature. In this case report, a 14 years old young boy with multilocular cystic renal cell carcinoma is presented and discussed with the relevant literature. Â  Key Words: Kidney, cancer, multilocular cysts, child, nephrectomy. Â 